Female hires and the success of start-up firms - Andrea Maria Weber; Christine Zulehner (Institute for the Study of Labor (IZA), 2009)
In this paper we investigate the relationship between females among the first hires of start-up companies and business success. Our results show that firms with female first hires have a higher share of female workers at the end of the first year after entry. Further, we find that firms with female first hires are more successful and stay longer in the market. We conclude that our results support the hypothesis that gender-diversity in leading positions is an advantage for start-up firms.
Keywords: J16; J71; L25; 330; Firm survival; profitability; female employment; discrimination; market test; matched employer-employee data; Unternehmensgründung; Personalbeschaffung; Frauenpolitik; Diversity Management; Unternehmensentwicklung; Erfolgsfaktor; Österreich